Review of research on the instance segmentation of cell images. (December 2022) - Wen, Tingxi; Tong, Binbin; Liu, Yu; Pan, Ting; Du, Yu; Chen, Yuping; Zhang, Shanshan
Highlights: This paper summarizes the important role of current computer-aided segmentation in cell segmentation. This paper systematically reviews image segmentation methods based on traditional and deep learning methods. This paper, from the three aspects of cell image weak label extraction, cell image instance segmentation, and cell internal structure segmentation, deep-learning-based cell image segmentation methods are analyzed and summarized. This paper summarizes the cell image instance segmentation and discusses its challenges and future developments. Abstract: The instance segmentation of cell images is the basis for conducting cell research and is of great importance for the study and diagnosis of pathologies. To analyze current situations and future developments in the field of cell image instance segmentation, this paper first systematically reviews image segmentation methods based on traditional and deep learning methods. Then, from the three aspects of cell image weak label extraction, cell image instance segmentation, and cell internal structure segmentation, deep-learning-based cell image segmentation methods are analyzed and summarized. Finally, cell image instance segmentation is summarized, and challenges and future developments are discussed.